Standardization of cost effective hybridization technique for hybrid seed production in okra (Abelmoschus esculentus) - SINGH, B; SINGH, P M; SANWAL, S K; PAL, A K (The Indian Journal of Agricultural Sciences, 2014)
Due to lack of stable male sterile system in okra [Abelmoschus esculentus (L.) Moench], hybrid seed production is still dependant on hand emasculation and pollination which is troublesome and labour intensive. Five hybridization techniques, viz. Hand emasculation and pollination (conventional method); One day premature bud cutting and pollination next day morning; Two days premature bud cutting and pollination next day morning; Mature bud cutting and pollination immediately thereafter and One day premature bud cutting and pollination next morning just after spray of 10% sugar solution were used in the study to standardize the cost effective hybridization technique based on two marker lines, viz. 678-2 (red pigmented with five ridges) and IIVR-10 (green fruited with seven ridges) as male parent and VRO-6 (green fruited with five ridges) as female parent. Percentage of fruit set was maximum in pigment based marker (60.82%) as compared to ridge based marker (57.40%), in general, and hand emasculation and pollination method in colour based marker, in particular, whereas number of seeds/fruit was recorded maximum (44.85) in one day premature bud cutting and pollination next morning. Time requirement for 100 flower bud hybridization (emasculation and pollination) was found maximum in hand emasculation and pollination method (198 minutes) and minimum in the treatment two days premature bud cutting and pollination next morning (69.5 minutes). Maximum time saving was observed in the treatment two days premature bud cutting and pollination next morning (64.88%) over hand ema sculation and pollination method, whereas minimum time saving over hand emasculation and pollination was observed in the treatment one day premature bud cutting and pollination next morning just after 10% sugar solution spray (44.72 %). As far as the economics of the 100 hybridized fruit set is concerned, the two days premature bud cutting and pollination next morning (Rupees 20.60) followed by one day premature bud cutting and pollination next morning (Rupees 21.82), which were significantly at par, were the most economical methods.